1977
DOI: 10.1083/jcb.72.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of lamellar body membranes into tubular myelin in alveoli of fetal rat lungs.

Abstract: Fluid-filled lumina of fetal rat lungs contain lamellar bodies (LBs) as well as tubular myelin (TM), both of which are thought to be stores of phospholipid-rich pulmonary surfactant. The alveolar epithelium is believed to secrete LBs, but neither the origin nor the mechanism of TM formation is entirely certain. The main objective of this study was to determine the relationship between secreted LBs and TM and to define membrane phenomena which occur during TM formation. I examined lung tissues of 20-21 day-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(122 citation statements)
references
References 38 publications
(51 reference statements)
8
112
1
1
Order By: Relevance
“…Immunocytochemistry was performed as previously described (52,53), and electromicroscopy was done by standard techniques (51). Cells were immunostained for SP-D in acid alcohol-fixed cultures, embedded in paraffin, and localized with polyclonal rabbit anti-rat SP-D IgG and FITC-labeled donkey antirabbit IgG (Jackson ImmunoResearch Laboratories, West Grove, PA) (52).…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry was performed as previously described (52,53), and electromicroscopy was done by standard techniques (51). Cells were immunostained for SP-D in acid alcohol-fixed cultures, embedded in paraffin, and localized with polyclonal rabbit anti-rat SP-D IgG and FITC-labeled donkey antirabbit IgG (Jackson ImmunoResearch Laboratories, West Grove, PA) (52).…”
Section: Methodsmentioning
confidence: 99%
“…MLBs are found in numerous cell types where they function in lipid storage and secretion (Schmitz and Mü ller, 1991). In lung type II alveolar cells, MLBs function as secretory granules whose exocytosis results in the deposition of the tubular myelin forms of surfactant on the surface of the alveolae (Hatasa and Nakamura, 1965;Ryan et al, 1975;Williams, 1977). The surfactant film over the alveolar epithelium regulates the surface tension at the air-cell interface and protects the alveola from collapse during respiration (Haagman and van Golde, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The spacing is somewhat irregular, probably due to high bilayer curvature, further discussed below. Williams (1977) in her pioneering study of TM formation observed periodicity along the ÔtransientÕ bilayers when LBs transform into TM. Particles were seen along one side of the bilayer with a diameter of about 8 nm, and a similar distance was reported to occur between particles.…”
Section: Discussionmentioning
confidence: 99%
“…at physiological conditions. In the previously mentioned studies (Nichols, 1976;Williams 1977;Young et al, 1992), chemical fixation was performed at room temperature, typically followed by post-fixation in osmium tetraoxide at 4°C and dehydration. At such fixation conditions, the hydrocarbon chain core of the lipid bilayer should crystallize (at least partly) according to a recent X-ray scattering/diffraction study .…”
Section: Discussionmentioning
confidence: 99%